Extracellular Biosynthesis of Silver Nanoparticles using Fusarium Graminearum and their Antimicrobial Activity - Hamzia Ali Ajah (Journal of Global Pharma Technology, 2018)
Synthesis of silver nanoparticles (AgNPs) has become a needful field of used science. Biological production silver nanoparticles have been more benefit in the formulation of new pharmaceutical products. In this study we report extracellular of silver nanoparticles by Fusarium graminaerum. The fungal aqueous mycelial extract when added aqueous silver nitrate solution (1Mm) leads to the manufacture of silver nanoparticles extracellular. The silver nanoparticles were characterized by Atomic force microscopy. In visual analysis color change of silver nitrate solution into brown signifies the development of silver nanoparticles. and the antibacterial activity of Ag NPs produced was evaluated against some local pathogenic microorganism isolates, Staphylococcus aureus , Pseudomonas aeruginosa , Streptococcus spp ,  Klebsiella spp , E. Coli and Candida albicans, using the well diffusion method. Our results showed that the Ag NPs were produced by Fusarium graminaerum and their sizes 94 nm. Moreover Ag NPs proved excellent antimicrobial activity with zone of inhibition ranged between 15 to 35 mm.Keywords: Silver nanoparticles, Fusarium graminaerum, Antimicrobial activity, Atomic Force Microscopy.